Russian Federation and the Development of Integration Processes in the modern World: Problems and Prospects - S. Yu. Kashkin (Евразийская интеграция: экономика, право, политика, 2020)
The aim of the article is to analyze the concept and essence of the modern integration relations development, which reflect 2 basic trends — rivalry and cooperation of states and integration interstate associations. The subject of the article is the characteristics and peculiarities of the modern integration law and its basic model — the law of the European Union, as well as the latest trend of integration relations in the post-Soviet space. The article uses general scientific, philosophical and special legal methods of knowledge, and is based on the material of integration law and related legal and political sciences. According to the results, the article assesses the possible prospects for the development of integration relations in the world, especially for the Russian Federation and Eurasian Economic Union.